2009
DOI: 10.1063/1.3269190
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring light emission properties of organic emitter by coupling to resonance-tuned silver nanoantenna arrays

Abstract: A convenient nanotechnique is reported to tailor the light emission properties of organic emitter poly͓2-methoxy-5-͑2Ј-ethyl-hexyloxy͒-p-phenylene vinylene͔ ͑MEH-PPV͒ by coupling to resonance-tuned silver nanoantenna arrays. It is revealed experimentally and theoretically that the enhanced photoluminescence from the MEH-PPV/silver nanoantenna complex may originate from the energy transfer effect in the surface plasmon resonance coupling between the MEH-PPV and silver nanocaps and from local electromagnetic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Frequently used templates are often produced from porous anodic alumina [PAA] or by lithography techniques [41,63,64]. The advantage of this method is avoidance of chemical peel-off, thus making incorporation of metallic NPs into EL LEDs possible.…”
Section: Fabricationmentioning
confidence: 99%
“…Frequently used templates are often produced from porous anodic alumina [PAA] or by lithography techniques [41,63,64]. The advantage of this method is avoidance of chemical peel-off, thus making incorporation of metallic NPs into EL LEDs possible.…”
Section: Fabricationmentioning
confidence: 99%
“…Experiments have confirmed the importance of overlapping between the localized surface plasmon resonance energy of the surface configuration and emission energy [1,6,7]. The type, shape, height, and density of the surface nanostructures determine the degree of enhancement [8].…”
Section: Introductionmentioning
confidence: 52%
“…To confirm, we try another method to remove the silver particles by HNO 3 and the outcome is almost the same as shown in (d). In fact, it has been demonstrated in our previous work that the PL efficiency of the MEH-PPV coupled silver nanostructures may originate from the energy transfer effect in the surface plasmon resonance coupling [7]. The plasmon resonance energy transfer process can occur through the dipole-dipole interaction between the resonating plasmon dipole in Ag caps and the MEH-PPV dipole.…”
Section: Resultsmentioning
confidence: 96%
“…8 The enhanced emission properties have been observed in many hybrids of the conjugated polymers/metal nanostructures, which are caused by scattering or plasmon resonance energy transfer. [9][10][11] The surface-plasmon (SP) enhanced energy transfer has been applied to improve the organic LEDs if the SP-excitation wavelength is close to both the donor emission and the acceptor absorption peaks. 12 If the SP energy of a nanoscale metal matches the emitted photon energy of an organic emitter, the resonance coupling can lead to the energy transfer from the organic emitter to the nanoscale metal surface to result in the quenching of the emission from the organic emitter.…”
mentioning
confidence: 99%
“…It has been found that the PL enhancement of an organic emitter is optimum in the hybrid prepared under this process condition. 9 In the paper, we selected two types of the conjugated polymers with different band gaps as the research objects. Regioregular poly [3-(2,5,8-trioxanonyl) thiophene] (P3TT) and poly(2,5-dioctyloxy-p-phenylene) (PPP) were prepared via Grignard metathesis (GRIM) polymerization.…”
mentioning
confidence: 99%